Adiposity change and mortality in middle-aged to older Chinese: an 8-year follow-up of the Guangzhou Biobank Cohort Study - Huang, Ying Yue (BMJ Open, 2020)
OBJECTIVE: To examine the associations of change in body mass index (BMI) and waist circumference (WC) over an average of 4 years with subsequent mortality risk in middle-aged to older Chinese. DESIGN: Prospective cohort study based on the Guangzhou Biobank Cohort Study. SETTING: Community-based sample. PARTICIPANTS: 17 773 participants (12 956 women and 4817 men) aged 50+ years. PRIMARY AND SECONDARY OUTCOME MEASURES: Primary outcome measure was all-cause mortality. Secondary outcome measures were cardiovascular disease (CVD) and cancer mortality. Causes of death were obtained via record linkage, and coded according to the International Classification of Diseases (tenth revision). RESULTS: 1424 deaths (53.4% women) occurred in the 17 773 participants (mean age 61.2, SD 6.8 years) during an average follow-up of 7.8 (SD=1.5) years, and 97.7% of participants did not have an intention of weight loss. Compared with participants with stable BMI, participants with BMI loss (>5%), but not gain, had a higher risk of all-cause mortality (HR=1.49, 95% CI 1.31 to 1.71), which was greatest in those who were underweight (HR=2.45, 95% CI 1.31 to 4.59). Similar patterns were found for WC. In contrast, for participants with a BMI of ≥27.5 kg/m(2), BMI gain, versus stable BMI, was associated with 89% higher risk of all-cause mortality (HR=1.89, 95% CI 1.25 to 2.88), 72% higher risk of CVD mortality (HR=1.72, 95% CI 0.80 to 3.72) and 2.27-fold risk of cancer mortality (HR=2.27, 95% CI 1.26 to 4.10). CONCLUSION: In older people, unintentional BMI/WC loss, especially in those who were underweight was associated with higher mortality risk. However, BMI gain in those with obesity showed excess risks of all-cause and cancer mortality, but not CVD mortality. Frequent monitoring of changes in body size can be used as an early warning for timely clinical investigations and interventions and is important to inform appropriate health management in older Chinese.